Water permeable brick with high water permeability and high strength and preparation method thereof

By using cement-free base slurry formula and optimized surface layer ratio, combined with industrial waste slag, mineral powder, fly ash and fiber, the problem of water-permeable bricks being difficult to take into account high permeability and high strength, achieving low cost and high strength Performance permeable brick preparation.

CN119118610APending Publication Date: 2024-12-13FOSHAN DONGPENG CERAMIC +4
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411258366.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing permeable bricks are difficult to take into account both high water permeability and high strength, and the cost is high, resulting in a decrease in strength due to the addition of industrial waste slag.

Method used

Using the base slurry formula that does not use cement as the cementitious material, activated calcium oxide in industrial waste residue, mineral powder and fly ash through sodium silicate to form calcium aluminate gel and calcium silicate gel, combined with calcium carbonate Whiskers and fibers optimize the raw material ratio of the bottom and surface layers to form a high pore structure to improve strength and water permeability.

Benefits of technology

It realizes that under the premise of reducing production costs, permeable bricks take into account both high water permeability and high strength, and have excellent wear resistance to meet actual use needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005034769040000171
    Figure BDA0005034769040000171
  • Figure BDA0005034769040000181
    Figure BDA0005034769040000181
Patent Text Reader

Abstract

The invention discloses a water permeable brick with high water permeability and high strength. The water permeable brick comprises a bottom layer and a surface layer which are sequentially arranged from bottom to top, the bottom layer slurry is prepared from the following raw materials in parts by mass: 50 to 55 parts of coarse aggregate, 30 to 35 parts of fine aggregate, 3 to 5 parts of mineral powder, 3 to 5 parts of industrial waste residue, 9 to 12 parts of fly ash, 3 to 5 parts of sodium silicate, 0.8 to 1 part of calcium carbonate whisker, 0.2 to 0.5 part of fiber, 0.7 to 1 part of retarder, 2 to 3 parts of water and 0.1 to 0.2 part of water reducing agent I; the surface layer slurry is prepared from the following raw materials in parts by mass: 55 to 65 parts of quartz sand, 15 to 20 parts of white cement, 0.1 to 0.5 part of pigment, 1 to 2 parts of water and 0.1 to 0.2 part of water reducing agent II. According to the high-water-permeability and high-strength water permeable brick provided by the invention, cement does not need to be used as a cementing material for the bottom layer slurry, and on the premise that the production cost is greatly reduced, the water permeable brick not only has high water permeability and high strength, but also has excellent wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of permeable bricks, and in particular to a permeable brick with high permeability and high strength and a preparation method thereof. Background Art

[0002] Permeable bricks are a kind of green and environmentally friendly building materials made of cement, sand, slag, fly ash and other materials under high pressure. They can make rainwater quickly penetrate into the ground, replenish soil moisture and groundwater, thereby ensuring soil moisture and improving the living conditions of urban ground plants and soil microorganisms. In addition, permeable bricks can also reduce urban drainage and flood control pressure, prevent public water from being polluted, and prevent water from accumulating on roads after rain, making it convenient for citizens to travel safely.

[0003] In order to save costs, the permeable bricks in the prior art mainly use a double layer of bottom layer and surface layer arranged in sequence from bottom to top; wherein the bottom layer is obtained by solidifying the bottom layer slurry, and the surface layer is obtained by applying and solidifying the surface layer slurry on the bottom layer. In order to improve the strength of the permeable bricks, the raw materials in the bottom layer slurry and the surface layer slurry in the prior art both use cement as a gelling material, resulting in a high cost of the permeable bricks. In order to further reduce production costs, industrial waste residues are usually added to the bottom layer slurry in the prior art, but the mechanical properties of the industrial waste residues themselves are poor, and their addition to the bottom layer slurry will reduce the strength of the permeable bricks.

[0004] In addition, the water permeability of permeable bricks mainly depends on their internal pore structure. The higher the porosity, the larger the pores, and the higher the water permeability. However, too high a porosity will reduce the density of the brick body and affect its strength, making it difficult for permeable bricks to have both high permeability and high strength. Summary of the invention

[0005] The purpose of the present invention is to propose a high-permeability and high-strength permeable brick, so that the bottom slurry does not need to use cement as a cementitious material, greatly reducing the production cost. The permeable brick can not only have high permeability and high strength at the same time, but also has excellent wear resistance, meeting actual use needs, so as to overcome the shortcomings of the prior art.

[0006] Another object of the present invention is to propose a method for preparing a high-permeability and high-strength permeable brick. The preparation method is simple and easy to operate, ensuring that the obtained permeable brick has a compressive strength of ≥40MPa, a flexural strength of ≥8MPa, a permeability coefficient of >0.03cm / s, and a grinding pit length of ≤35mm. It can not only take into account high permeability and high strength at the same time, but also has excellent wear resistance.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] A high-permeability and high-strength permeable brick, comprising a bottom layer and a surface layer arranged in sequence from bottom to top; the bottom layer is obtained by solidifying the bottom layer slurry, and the surface layer is obtained by solidifying the surface layer slurry;

[0009] Calculated by weight, the base slurry includes the following raw materials: 50-55 parts of coarse aggregate, 30-35 parts of fine aggregate, 3-5 parts of mineral powder, 3-5 parts of industrial waste slag, 9-12 parts of fly ash, 3-5 parts of sodium silicate, 0.8-1 part of calcium carbonate whisker, 0.2-0.5 part of fiber, 0.7-1 part of retarder, 2-3 parts of water and 0.1-0.2 part of water reducer I; the chemical composition of the industrial waste slag includes silicon dioxide, aluminum oxide and calcium oxide;

[0010] Calculated by mass, the surface layer slurry includes the following raw materials: 55-65 parts of quartz sand, 15-20 parts of white cement, 0.1-0.5 parts of pigment, 1-2 parts of water and 0.1-0.2 parts of water reducer II; wherein the white cement is P.II525 cement, and the mesh size of the quartz sand is 20-40 meshes.

[0011] Furthermore, the industrial waste slag is water-quenched slag, and the chemical composition of the water-quenched slag, calculated by mass percentage, includes 30-35% silicon dioxide, 15-20% aluminum oxide and 35-40% calcium oxide, and the remainder is ferric oxide, magnesium oxide, sodium oxide, titanium dioxide, potassium oxide, manganese oxide and sulfur trioxide;

[0012] The particle size of the water-quenched slag is less than 2 mm.

[0013] Furthermore, the aspect ratio of the calcium carbonate whisker is 40-60, the length of the fiber is 6-12 mm, and the diameter is 45-190 μm.

[0014] Furthermore, the fly ash is Grade III fly ash;

[0015] The modulus of the sodium silicate is 1.2 to 1.4.

[0016] Furthermore, the thickness of the bottom layer is 50-55 mm, and the thickness of the surface layer is 5-10 mm.

[0017] Furthermore, the coarse aggregate is recycled aggregate, and the particle size of the recycled aggregate is 5 to 10 mm;

[0018] The fine aggregate is river sand, and the particle size of the river sand is 0.1-0.5 mm. Calculated by mass percentage, the mud content of the river sand is ≤3%.

[0019] Further, the retarder includes zinc nitrate and sodium gluconate;

[0020] Calculated by mass ratio, the mixing ratio of the zinc nitrate and the sodium gluconate is (6-8): (2-4).

[0021] A method for preparing a high-permeability and high-strength permeable brick, which is used to prepare the above-mentioned low-cost and high-strength imitation stone surface permeable brick, comprises the following steps:

[0022] A. Preparation of bottom slurry:

[0023] After mixing the formulated amount of mineral powder, industrial waste slag and fly ash uniformly, calcium carbonate whiskers, part of the formulated amount of water and fiber are added in sequence, and mixed uniformly to obtain a mixture;

[0024] The coarse aggregate and fine aggregate of the formula amount are mixed evenly, and then part of the formula amount of water is added and stirred evenly, and then the mixture is added to obtain an intermediate slurry;

[0025] After uniformly mixing the formulated amount of sodium silicate, retarder, water reducer I and the remaining formulated amount of water, the intermediate slurry is added and stirred to obtain the bottom slurry;

[0026] B. Preparation of surface slurry:

[0027] After mixing the formulated amount of quartz sand and part of the formulated amount of water evenly, add the formulated amount of white cement, pigment, water reducing agent II and the remaining formulated amount of water, and mix evenly to obtain the surface slurry;

[0028] C. Preparation of low-cost and high-strength imitation stone surface permeable bricks:

[0029] The bottom layer slurry is injected into the mold and initially pressed to form the bottom layer;

[0030] The surface layer slurry is injected on the top of the bottom layer in the mold, and the surface layer is formed by re-pressing to obtain the middle brick;

[0031] After the middle brick is sealed and steam cured, a high-permeability and high-strength permeable brick is obtained.

[0032] Furthermore, in step C, the initial pressure of the initial pressure is 3-5 MPa, and the initial pressure time is 0.5-1 s;

[0033] The re-pressing pressure of the re-pressing is 4-6 MPa, and the initial pressing time is 0.5-1 s;

[0034] The curing temperature of the steam curing is 40-60° C., and the curing time is 8-12 hours.

[0035] Furthermore, in step C, the compressive strength of the permeable brick is ≥40MPa, the flexural strength is ≥8MPa, the water permeability coefficient is >0.03cm / s, and the grinding pit length is ≤35mm.

[0036] The technical solution provided by the embodiments of the present application may have the following beneficial effects:

[0037] 1. The chemical composition of industrial waste residue includes silicon dioxide, aluminum oxide and calcium oxide, and the chemical composition of mineral powder and fly ash materials themselves also includes silicon dioxide, aluminum oxide and calcium oxide. When sodium silicate is added to the base slurry formula, sodium silicate undergoes hydrolysis reaction with water to generate hydroxide ions, making the slurry system alkaline; at the same time, the calcium oxide in industrial waste residue, mineral powder and fly ash exists in the form of active calcium oxide. In an aqueous and alkaline environment, the activity of the active calcium oxide in industrial waste residue, mineral powder and fly ash will be activated to form calcium hydroxide, increasing the alkalinity of the system. In addition, the silicon dioxide in industrial waste residue, mineral powder and fly ash exists in the form of active silicon dioxide and inert silicon dioxide, and both active silicon dioxide and inert silicon dioxide exist in the form of silicon-oxygen network structure, and aluminum oxide exists in the form of active aluminum oxide, and active aluminum oxide exists in the form of aluminum-oxygen network structure. Under the action of strong alkali, the silicon-oxygen chains in the silicon-oxygen network structure and the aluminum-oxygen chains in the aluminum-oxygen network structure are depolymerized to generate a large number of depolymerized monomer ions, so that the active silicon dioxide, inert silicon dioxide and active aluminum oxide in the industrial waste slag are fully released, that is, the activity of active silicon dioxide, inert silicon dioxide, active aluminum oxide and active calcium oxide in the industrial waste slag is activated; at the same time, the above-mentioned monomer ions undergo condensation reaction again in an alkaline environment to generate aluminates and silicates, and the aluminates and silicates can react with the calcium hydroxide produced by the activation of the activity of active calcium oxide in the industrial waste slag, mineral powder and fly ash in the system, thereby forming calcium aluminate gel and calcium silicate gel. Calcium aluminate gel and calcium silicate gel can replace cement as a cementitious material to better wrap and bond the coarse aggregate and fine aggregate in the base slurry formula, ensure the strength of the base slurry after curing, and give the permeable brick a higher strength.

[0038] 2. The raw materials in the bottom slurry also include calcium carbonate whiskers and fibers. The slender fiber shape of calcium carbonate whiskers not only gives it high strength and high modulus, but also helps to improve the toughness and flexural resistance of the permeable brick. In addition, the good mechanical properties and reinforcing effect of the fiber itself are also conducive to improving the strength of the permeable brick. Therefore, this technical solution helps to further improve the strength of the permeable brick by adding calcium carbonate whiskers and fibers to the bottom slurry formula, and further solves the technical problem in the prior art that the strength of the permeable brick is reduced due to the addition of industrial waste residues to the bottom slurry formula.

[0039] 3. Coarse aggregate and fine aggregate are not only the key to form the skeleton structure, but also form gaps in the bottom slurry formula to ensure the basis of water permeability. In addition, the cross-over and overlap between calcium carbonate whiskers, fibers, coarse aggregate and fine aggregate in the bottom slurry formula are conducive to the formation of more porous structures, which increases the porosity of the permeable brick without reducing its strength, making it both highly permeable and high-strength. DETAILED DESCRIPTION

[0040] The technical solution provides a high-permeability and high-strength permeable brick, comprising a bottom layer and a surface layer arranged in sequence from bottom to top; the bottom layer is obtained by solidifying the bottom layer slurry, and the surface layer is obtained by solidifying the surface layer slurry;

[0041] Calculated by weight, the base slurry includes the following raw materials: 50-55 parts of coarse aggregate, 30-35 parts of fine aggregate, 3-5 parts of mineral powder, 3-5 parts of industrial waste slag, 9-12 parts of fly ash, 3-5 parts of sodium silicate, 0.8-1 part of calcium carbonate whisker, 0.2-0.5 part of fiber, 0.7-1 part of retarder, 2-3 parts of water and 0.1-0.2 part of water reducer I; the chemical composition of the industrial waste slag includes silicon dioxide, aluminum oxide and calcium oxide;

[0042] Calculated by mass, the surface layer slurry includes the following raw materials: 55-65 parts of quartz sand, 15-20 parts of white cement, 0.1-0.5 parts of pigment, 1-2 parts of water and 0.1-0.2 parts of water reducer II; wherein the white cement is P.II525 cement, and the mesh size of the quartz sand is 20-40 meshes.

[0043] In view of the technical problems in the prior art that permeable bricks are high in cost and difficult to achieve both high permeability and high strength, the present technical solution proposes a permeable brick with high permeability and high strength. By designing the ratio of the base slurry and the surface slurry and optimizing the raw materials, it is possible to eliminate the need for cement as a cementitious material in the base slurry, thereby greatly reducing the production cost. The permeable brick can not only achieve both high permeability and high strength, but also has excellent wear resistance to meet actual use needs.

[0044] Specifically, the permeable bricks in the prior art mainly use a double layer of base layer and surface layer arranged in sequence from bottom to top; the base layer is obtained by applying and solidifying the base layer slurry, and the surface layer is obtained by applying and solidifying the surface layer slurry; in order to improve the strength of the permeable bricks, the raw materials in the base layer slurry and the surface layer slurry in the prior art both use cement as the cementitious material, resulting in a higher cost of the permeable bricks.

[0045] The bottom slurry in the technical solution includes coarse aggregate, fine aggregate, mineral powder, industrial waste slag, fly ash, sodium silicate, calcium carbonate whisker, fiber, retarder, water and water reducer I. The chemical composition of industrial waste slag includes silicon dioxide, aluminum trioxide and calcium oxide, and the chemical composition of mineral powder and fly ash materials themselves also includes silicon dioxide, aluminum trioxide and calcium oxide. When sodium silicate is added to the bottom slurry formula, sodium silicate and water undergo hydrolysis reaction to generate hydroxide ions to make the slurry system alkaline; at the same time, the calcium oxide in industrial waste slag, mineral powder and fly ash exists in the form of active calcium oxide. In an aqueous and alkaline environment, the activity of the active calcium oxide in the industrial waste slag, mineral powder and fly ash will be activated to form calcium hydroxide, increasing the alkalinity of the system. In addition, the silica in industrial waste slag, mineral powder and fly ash exists in the form of active silica and inert silica, and both active silica and inert silica exist in the form of silicon-oxygen network structure. Alumina exists in the form of active alumina, and active alumina exists in the form of aluminum-oxygen network structure. Under the action of strong alkali, the silicon-oxygen chains in the silicon-oxygen network structure and the aluminum-oxygen chains in the aluminum-oxygen network structure are depolymerized to generate a large number of depolymerized monomer ions, so that the active silicon dioxide, inert silicon dioxide and active aluminum oxide in the industrial waste slag are fully released, that is, the activity of active silicon dioxide, inert silicon dioxide, active aluminum oxide and active calcium oxide in the industrial waste slag is activated; at the same time, the above monomer ions undergo polycondensation reaction again in an alkaline environment to generate aluminates and silicates, and aluminates and silicates can react with calcium hydroxide, the product of the activated activity of active calcium oxide in industrial waste slag, mineral powder and fly ash in the system, to form calcium aluminate gel and calcium silicate gel, which can replace cement as a cementitious material to better wrap and bond the coarse aggregate and fine aggregate in the bottom slurry formula, ensure the strength of the bottom slurry after curing, and give the permeable brick a higher strength. At the same time, since cement is not used as a cementitious material in the bottom slurry formula, it not only greatly reduces the cost, but also reduces the risk of alkali efflux caused by cement hydration. In addition, in the present technical solution, sodium silicate is used as an alkaline activator to activate silicon dioxide, aluminum oxide and calcium oxide in industrial waste slag, and finally calcium aluminate gel and calcium silicate gel that can replace cement are generated, thereby making the permeable bricks have higher strength, solving the technical problem in the prior art that the strength of the permeable bricks is reduced due to the addition of industrial waste slag to the base slurry formula.

[0046] In addition, the raw materials in the bottom slurry in the technical solution also include calcium carbonate whiskers and fibers. The slender fiber shape of the calcium carbonate whiskers not only gives it high strength and high modulus, but also helps to improve the toughness and flexural resistance of the permeable bricks. In addition, the good mechanical properties and reinforcing effect of the fibers themselves are also conducive to improving the strength of the permeable bricks. Therefore, the technical solution is conducive to further improving the strength of the permeable bricks by adding calcium carbonate whiskers and fibers to the bottom slurry formula, and further solves the technical problem in the prior art that the strength of the permeable bricks is reduced due to the addition of industrial waste residues to the bottom slurry formula.

[0047] Furthermore, the water permeability of permeable bricks mainly depends on the pore structure inside them. The higher the porosity, the larger the pores, and the higher the water permeability. However, too high a porosity will reduce the density of the brick body and affect its strength, making it difficult for permeable bricks to have both high permeability and high strength.

[0048] The bottom slurry in the technical solution also includes coarse aggregate and fine aggregate, wherein the coarse aggregate and fine aggregate are not only the key to form the skeleton structure, but also enable the bottom slurry formula to form gaps, ensuring the basis of water permeability. In addition, the mutual intersection and coverage between the calcium carbonate whiskers, fibers, coarse aggregates and fine aggregates in the bottom slurry formula are conducive to forming more porous structures, which increases the porosity of the permeable brick without reducing its strength, so that it has both high water permeability and high strength.

[0049] In addition, the base slurry formula also includes retarders and water reducers. Among them, the retarder is helpful to slow down the speed at which silica, aluminum oxide and calcium oxide in the system are stimulated to form calcium aluminate gel and calcium silicate gel in an alkaline system, preventing the calcium aluminate gel and calcium silicate gel from solidifying quickly, so that the base slurry can maintain plasticity for a long time and ensure its construction performance. The water reducer can reduce the use of water in the base slurry formula while ensuring the fluidity of the base slurry and improving the strength of the base, thereby reducing the negative effects such as shrinkage cracks in the base and improving the durability of the base.

[0050] Further, according to the mass percentage, the bottom slurry in the technical solution includes 50-55 parts of coarse aggregate, 30-35 parts of fine aggregate, 3-5 parts of mineral powder, 3-5 parts of industrial waste slag, 9-12 parts of fly ash, 3-5 parts of sodium silicate, 0.8-1 parts of calcium carbonate whisker, 0.2-0.5 parts of fiber, 0.7-1 parts of retarder, 2-3 parts of water and 0.1-0.2 parts of water reducer I. The addition amount of mineral powder, industrial waste slag and fly ash is matched to make the bottom layer have high strength without using cement; the addition amount of coarse aggregate, fine aggregate and industrial waste slag is matched to increase the porosity of the bottom slurry and have high water permeability.

[0051] Therefore, the technical solution, through the coordination of raw materials such as coarse aggregate, fine aggregate, mineral powder, industrial waste slag, fly ash, sodium silicate, calcium carbonate whisker, fiber, retarder, water and water reducer I, enables the prepared base layer to have both high permeability and high strength without using cement as a cementitious material, thus greatly reducing the production cost.

[0052] Since the permeability and strength of permeable bricks are not only related to the underlying slurry, but their related performance is also greatly affected by the surface layer, ordinary surface slurry cannot meet the requirements of this technical solution. Therefore, this technical solution also optimizes the formula of the surface slurry.

[0053] Specifically, the raw materials of the surface slurry include quartz sand, white cement, pigment, water and water reducing agent II; the quartz sand in the surface slurry constitutes the key to its skeleton structure, and the skeleton formed by the mutual extrusion of quartz sand is the basis of the high porosity of the surface layer, which makes the surface layer have good water permeability, thereby ensuring the high water permeability of the permeable brick. In addition, compared with ordinary sand and stone raw materials as aggregates, quartz sand has high strength and high wear resistance, which can ensure the high strength and high wear resistance of the surface layer, thereby ensuring the high strength and high wear resistance of the permeable brick.

[0054] Furthermore, when the mesh number of quartz sand is too large, it is not conducive to its combination with white cement to obtain a relatively fine permeable brick surface layer, affecting the aesthetics of the permeable brick; when the mesh number of quartz sand is too small, the amount of cement required to be filled increases, and the increase in cement not only increases the cost of the permeable brick, but also reduces the wear resistance of the surface layer. At the same time, the porosity of the skeleton formed by the mutual extrusion of quartz sand is low, affecting the permeability. Therefore, in a preferred embodiment of the present technical solution, by adding quartz sand with a mesh number of 20 to 40 between coarse sand and medium sand to the formula, it is combined with white cement to ensure the decorative effect, permeability and wear resistance of the permeable brick.

[0055] In addition, since the surface layer not only needs to consider its practical performance, but also its decorative effect, and since mineral powder, industrial waste slag and fly ash are generally dark raw materials, when the above raw materials are used as raw materials in the surface layer slurry to form a cementitious material in an alkaline system, due to the dark color of the above raw materials, it is difficult to meet the requirements of the surface layer for the decorative effect. Therefore, the surface layer slurry in the technical solution uses white cement as a cementitious material to bond the various components in the surface layer slurry together to ensure the strength and decorative effect of the prepared surface layer.

[0056] When the surface slurry with increased porosity forms the surface layer of the permeable brick, due to its high porosity, its contact area with the external environment is increased, which makes the aging phenomenon of the surface slurry aggravated under the action of dynamic water pressure and ultraviolet rays. At the same time, due to the thinning of the thickness of the structural layer, its interior will produce greater tensile and shear stresses than the traditional surface layer, and the ordinary white cement has insufficient adhesion to the skeleton structure, so this scheme specifically uses P.Ⅱ525 cement to ensure the performance of the surface layer. Compared with ordinary white cement, P.Ⅱ525 cement has the advantages of high bonding strength and strong compressive resistance. This scheme uses P.Ⅱ525 cement as raw material, which is conducive to improving the wrapping of white cement on quartz sand, ensuring the high strength of the surface slurry, and ensuring the performance of the permeable brick.

[0057] In addition, the raw materials of the surface slurry also include pigments, which can give the surface slurry color and make the surface layer have rich colors, thereby giving the permeable brick a better decorative effect. It should be noted that the pigment in this technical solution can be a red pigment, a yellow raw material or other color pigments, which can be added according to actual needs, and the specific type is not limited here.

[0058] More specifically, calculated by mass, the surface layer slurry includes 55-60 parts of quartz sand, 15-20 parts of white cement, 0.1-0.5 parts of pigment, 1-2 parts of water and 0.1-0.2 parts of water reducer II. By combining the added amounts of each raw material in the surface layer slurry formula, the surface layer not only has a good decorative effect, but also has high strength, high wear resistance and high water permeability, thereby ensuring that the permeable bricks are both decorative and applicable, and better meet the actual use needs.

[0059] Preferably, the water reducer I and the water reducer II are both polycarboxylate water reducers.

[0060] In a preferred embodiment of the present technical solution, both water reducer I and water reducer II are polycarboxylic acid water reducers, which can reduce water consumption on the one hand and improve the strength of the permeable bricks on the other hand to ensure the performance of the product.

[0061] Preferably, the water-cement ratio of the bottom slurry is 0.3 to 0.4 in terms of mass ratio;

[0062] According to the mass ratio, the water-cement ratio of the surface layer slurry is 0.3-0.4.

[0063] When the water-cement ratio is too small, the slurry is dry and its bonding performance is poor, which is not conducive to the bonding and wrapping of aggregates, thereby reducing the strength of the permeable bricks; when the water-cement ratio is too large, the slurry fluidity is too large, and the slurry will block the pores of the permeable bricks, reducing its permeability. Therefore, in a preferred embodiment of the present technical solution, the water-cement ratio of the bottom slurry and the water-cement ratio of the surface slurry are both limited to 0.3-0.4, thereby ensuring the strength and permeability of the permeable bricks. It should be noted that the water-cement ratio in the bottom slurry refers to the ratio of the weight of water in the bottom slurry to the total weight of mineral powder, industrial waste slag and fly ash, and the water-cement ratio in the surface slurry refers to the ratio of the weight of water in the surface slurry to the weight of cement, and the size of the ratio determines the fluidity of the slurry.

[0064] It is further explained that the industrial waste slag is water-quenched slag, and the chemical composition of the water-quenched slag, calculated by mass percentage, includes 30-35% silicon dioxide, 15-20% aluminum oxide and 35-40% calcium oxide, and the remainder is ferric oxide, magnesium oxide, sodium oxide, titanium dioxide, potassium oxide, manganese oxide and sulfur trioxide;

[0065] The particle size of the water-quenched slag is less than 2 mm.

[0066] In a preferred embodiment of the present technical solution, the industrial waste slag is water-quenched slag, and the chemical composition of the water-quenched slag includes 30-35% silicon dioxide, 15-20% aluminum oxide and 35-40% calcium oxide, and the remainder is iron oxide, magnesium oxide, sodium oxide, titanium dioxide, potassium oxide, manganese oxide and sulfur trioxide. It can be seen from its composition table that it contains a large amount of silicon dioxide, aluminum oxide and calcium oxide, which is beneficial to improve the strength and permeability of the permeable bricks made using the industrial waste slag.

[0067] Furthermore, the particle size of the water-quenched slag is less than 2 mm, which is beneficial to improving its utilization rate, stimulating its activity, and increasing the strength of the permeable bricks.

[0068] It is further described that the aspect ratio of the calcium carbonate whisker is 40-60, the length of the fiber is 6-12 mm, and the diameter is 45-190 μm.

[0069] In this technical solution, by further optimizing the aspect ratio of the calcium carbonate whiskers and the length and diameter of the fibers, it is beneficial to form more pore structures and ensure the performance of the permeable bricks while ensuring that the strength of the two is improved. It should be noted that the aspect ratio of the calcium carbonate whiskers refers to the ratio of their length to their diameter.

[0070] Preferably, the fiber includes at least one of PVA fiber and PE fiber.

[0071] It is further specified that the fly ash is Grade III fly ash;

[0072] The modulus of the sodium silicate is 1.2 to 1.4.

[0073] Since Grade III fly ash has a large specific surface area and high contents of silicon dioxide, aluminum oxide and calcium oxide, it is beneficial to increase the content of aluminate and silicate generated in an alkaline system, thereby improving the strength of permeable bricks.

[0074] Furthermore, the modulus of sodium silicate refers to the molar ratio of silicon dioxide to sodium oxide in its molecule. When the modulus of sodium silicate is too high, its solid form may be more difficult to dissolve in water, requiring higher temperature or pressure conditions to dissolve, resulting in difficulties in production and processing. An excessively high modulus may result in poor swelling and weak permeability of sodium silicate, which is not conducive to bonding. When the modulus of sodium silicate is too low, its viscosity may be low and its bonding performance is weak, which is not conducive to adhesion to coarse aggregate and fine aggregate. At the same time, an excessively low modulus may shorten the hardening time of sodium silicate, which is not conducive to the construction of the bottom slurry. Therefore, in a preferred embodiment of the present technical solution, the modulus of sodium silicate is limited to 1.2 to 1.4, ensuring the construction performance and strength of the bottom slurry, thereby ensuring the performance of the permeable brick.

[0075] Further description: the thickness of the bottom layer is 50-55 mm, and the thickness of the surface layer is 5-10 mm.

[0076] The bottom slurry formula in the present technical solution does not contain cement, so its cost is lower than that of the surface slurry. Therefore, in a preferred embodiment of the present technical solution, by limiting the thickness of the bottom layer and the thickness of the surface layer, the thickness of the bottom layer is much higher than the thickness of the surface layer, so that the amount of cement in the overall permeable brick formula is less than 10%, which is more conducive to reducing its production cost. In addition, when the thickness of the surface layer is too thin, the quartz sand is partially exposed, affecting the aesthetics of the permeable brick; when the thickness of the surface layer is too thick, it is easy to stick and fall off, affecting the strength and wear resistance of the surface layer. Therefore, in the present technical solution, the thickness of the surface layer is limited to 5 to 10 mm, which is also conducive to ensuring its aesthetics, strength and wear resistance.

[0077] It is further described that the coarse aggregate is recycled aggregate, and the particle size of the recycled aggregate is 5 to 10 mm;

[0078] The fine aggregate is river sand, and the particle size of the river sand is 0.1-0.5 mm. Calculated by mass percentage, the mud content of the river sand is ≤3%.

[0079] In a preferred embodiment of the present technical solution, the preferred aggregate is recycled aggregate, which is conducive to further reducing the production cost of permeable bricks. In addition, the particle size of the recycled aggregate is 5 to 10 mm; the fine aggregate is river sand, and the particle size of the river sand is 0.1 to 0.5 mm, and the mud content of the river sand is limited, which is conducive to ensuring the porosity and strength of the bottom slurry, so that the bottom layer prepared using the bottom slurry has good permeability and strength, thereby ensuring the performance of the permeable brick. It should be noted that the recycled aggregate of the present technical solution can be concrete recycled aggregate, etc., and the specific type is not limited here.

[0080] It is further stated that the retarder includes zinc nitrate and sodium gluconate;

[0081] Calculated by mass ratio, the mixing ratio of the zinc nitrate and the sodium gluconate is (6-8): (2-4).

[0082] In a preferred embodiment of the present technical solution, the retarder includes zinc nitrate and sodium gluconate, wherein the zinc nitrate is a coated retarder, and the zinc hydroxide formed by its zinc ions can react with the calcium hydroxide produced after the activity of calcium oxide in industrial waste slag, mineral powder and fly ash in the system is activated to form calcium zinc hydrate, and the calcium zinc hydrate covers the surface of the gelling material in the system to reduce the solidification rate of calcium aluminate gel and calcium silicate gel; sodium gluconate is a neutralizing retarder, and can react with the calcium aluminate gel and calcium silicate gel in the system to form insoluble metal salts to play a retarding effect, and the two cooperate with each other to effectively extend the construction timeliness of the base slurry and ensure its construction performance.

[0083] Furthermore, the mass mixing ratio of zinc nitrate and sodium gluconate is (6-8):(2-4). By limiting the ratio of zinc nitrate and sodium gluconate, the retarder effect is optimized, ensuring that the construction performance of the base slurry reaches the best.

[0084] A method for preparing a high-permeability and high-strength permeable brick, which is used to prepare the above-mentioned low-cost and high-strength imitation stone surface permeable brick, comprises the following steps:

[0085] A. Preparation of bottom slurry:

[0086] After mixing the formulated amount of mineral powder, industrial waste slag and fly ash uniformly, calcium carbonate whiskers, part of the formulated amount of water and fiber are added in sequence, and mixed uniformly to obtain a mixture;

[0087] The coarse aggregate and fine aggregate of the formula amount are mixed evenly, and then part of the formula amount of water is added and stirred evenly, and then the mixture is added to obtain an intermediate slurry;

[0088] After uniformly mixing the formulated amount of sodium silicate, retarder, water reducer I and the remaining formulated amount of water, the intermediate slurry is added and stirred to obtain the bottom slurry;

[0089] B. Preparation of surface slurry:

[0090] After mixing the formulated amount of quartz sand and part of the formulated amount of water evenly, add the formulated amount of white cement, pigment, water reducing agent II and the remaining formulated amount of water, and mix evenly to obtain the surface slurry;

[0091] C. Preparation of low-cost and high-strength imitation stone surface permeable bricks:

[0092] The bottom layer slurry is injected into the mold and initially pressed to form the bottom layer;

[0093] The surface layer slurry is injected on the top of the bottom layer in the mold, and the surface layer is formed by re-pressing to obtain the middle brick;

[0094] After the middle brick is sealed and steam cured, a high-permeability and high-strength permeable brick is obtained.

[0095] This technical solution also proposes a high-permeability and high-strength permeable brick, which has simple steps and strong operability, and is conducive to avoiding the related performance of the permeable brick during the preparation process.

[0096] Specifically, in the technical solution, when preparing the bottom slurry, part of the water is used to first wet the coarse aggregate and the fine aggregate, so that the coarse aggregate and the fine aggregate are more easily wrapped and adhered by the cementitious material, thereby ensuring the strength of the permeable brick. In addition, when preparing the surface slurry, part of the water is also used to first wet the quartz sand, so that the quartz sand is more easily wrapped and adhered by the cement, which is conducive to ensuring the strength and wear resistance of the permeable brick.

[0097] Further, in step C, the initial pressure of the initial pressure is 3-5 MPa, and the initial pressure time is 0.5-1 s;

[0098] The re-pressing pressure of the re-pressing is 4-6 MPa, and the initial pressing time is 0.5-1 s;

[0099] The curing temperature of the steam curing is 40-60° C., and the curing time is 8-12 hours.

[0100] In a preferred embodiment of the present technical solution, by limiting the initial pressing pressure, initial pressing time, re-pressing pressure and initial pressing time in step C, it is beneficial to improve the bonding strength between the base layer and the surface layer, while also avoiding excessive initial pressing pressure and re-pressing pressure, which may cause the brick body to break.

[0101] Furthermore, by limiting the curing temperature and curing time, the cement in the surface slurry can be fully hydrated, so that the strength of the permeable bricks can be gradually increased during the curing process, and the permeable bricks can have high strength after curing. At the same time, it also avoids the curing time being too long, which increases the possibility of alkali efflorescence of the permeable bricks.

[0102] Further explanation: in step C, the compressive strength of the permeable brick is ≥40MPa, the flexural strength is ≥8MPa, the permeability coefficient is >0.03cm / s, and the grinding pit length is ≤35mm.

[0103] In step C of the present technical solution, the obtained permeable brick has a compressive strength of ≥40MPa, a flexural strength of ≥8MPa, a permeability coefficient of >0.03cm / s, and a grinding pit length of ≤35mm. It not only has high permeability and high strength, but also has excellent wear resistance to meet the use requirements.

[0104] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0105] Example 1

[0106] In this embodiment, the bottom slurry includes the following raw materials calculated by weight: 50 parts of recycled concrete aggregate with a particle size of 5 mm, 35 parts of river sand with a particle size of 0.1 mm and a mud content of ≤3%, 3 parts of mineral powder, 5 parts of water-quenched slag, 9 parts of Class III fly ash, 5 parts of sodium silicate with a modulus of 1.2, 1 part of calcium carbonate whisker with an aspect ratio of 50, 0.2 parts of PVA fiber with a length of 12 mm and a diameter of 150 μm, 0.7 parts of retarder, 2.2 parts of water and 0.1 parts of polycarboxylate water reducer; calculated by weight: According to the calculation of mass ratio, the chemical composition of the water-quenched slag includes 30.16% silicon dioxide, 16.41% aluminum oxide, 39.48% calcium oxide, 0.44% iron oxide, 9.40% magnesium oxide, 0.51% sodium oxide, 1.67% titanium dioxide, 0.38% potassium oxide, 0.53% manganese oxide and 1.02% sulfur trioxide; the particle size of the water-quenched slag is 1.5mm; the retarder includes zinc nitrate and sodium gluconate, and according to the mass ratio, the mixing ratio of zinc nitrate and sodium gluconate is 7:3;

[0107] Calculated by mass, the surface layer slurry includes the following raw materials: 60 parts of 30-mesh quartz sand, 18 parts of P.Ⅱ525 cement, 0.2 parts of red pigment, 1 part of water and 0.1 parts of polycarboxylic acid water reducer.

[0108] The method for preparing the high-permeability and high-strength permeable brick of this embodiment comprises the following steps:

[0109] A. Preparation of bottom slurry:

[0110] After mixing the formulated amount of mineral powder, industrial waste slag and fly ash evenly, calcium carbonate whiskers, 20% of the formulated amount of water and fiber are added in sequence, and mixed evenly to obtain a mixture;

[0111] Mix the formula amount of recycled aggregate and river sand evenly, add 30% of the formula amount of water and stir evenly, then add the mixture to obtain an intermediate slurry;

[0112] After uniformly mixing the formulated amount of sodium silicate, zinc nitrate, sodium gluconate, polycarboxylate water reducer and the remaining formulated amount of water, the intermediate slurry is added and stirred to obtain the bottom slurry;

[0113] B. Preparation of surface slurry:

[0114] After mixing the formulated quartz sand and 40% of the formulated water evenly, add the formulated P.Ⅱ525 cement, red pigment, polycarboxylic acid water reducer and the remaining formulated water, and mix evenly to obtain the surface slurry;

[0115] C. Preparation of low-cost and high-strength imitation stone surface permeable bricks:

[0116] The bottom layer slurry was injected into the mold and pressed at a pressure of 3 Mpa for 1 second to form a bottom layer with a thickness of 50 mm;

[0117] The surface layer slurry is injected on the top of the bottom layer in the mold, and pressed for 0.5s at a pressure of 4Mpa to form a surface layer with a thickness of 5mm to obtain an intermediate brick; after the intermediate brick is sealed and cured at 50°C for 10h, a highly permeable and high-strength permeable brick is obtained.

[0118] Example 2

[0119] In this embodiment, the bottom slurry includes the following raw materials calculated by weight: 55 parts of recycled concrete aggregate with a particle size of 8 mm, 30 parts of river sand with a particle size of 0.3 mm and a mud content of ≤3%, 3.8 parts of mineral powder, 4 parts of water-quenched slag, 10 parts of Class III fly ash, 4 parts of sodium silicate with a modulus of 1.3, 0.8 parts of calcium carbonate whiskers with an aspect ratio of 40, 0.3 parts of PE fibers with a length of 6 mm and a diameter of 50 μm, 1 part of retarder, 2 parts of water and 0.2 parts of polycarboxylate water reducer; calculated by weight percentage According to the calculation of mass ratio, the chemical composition of the water-quenched slag includes 30.16% silicon dioxide, 16.41% aluminum oxide, 39.48% calcium oxide, 0.44% iron oxide, 9.40% magnesium oxide, 0.51% sodium oxide, 1.67% titanium dioxide, 0.38% potassium oxide, 0.53% manganese oxide and 1.02% sulfur trioxide; the particle size of the water-quenched slag is 1.5mm; the retarder includes zinc nitrate and sodium gluconate, and according to the mass ratio, the mixing ratio of zinc nitrate and sodium gluconate is 6:4;

[0120] Calculated by mass, the surface layer slurry includes the following raw materials: 55 parts of 40-mesh quartz sand, 20 parts of P.Ⅱ525 cement, 0.3 parts of yellow pigment, 1.5 parts of water and 0.15 parts of polycarboxylic acid water reducer.

[0121] The method for preparing the high-permeability and high-strength permeable brick of this embodiment comprises the following steps:

[0122] A. Preparation of bottom slurry:

[0123] After mixing the formulated amount of mineral powder, industrial waste slag and fly ash evenly, calcium carbonate whiskers, 25% of the formulated amount of water and fiber are added in sequence, and mixed evenly to obtain a mixture;

[0124] Mix the formula amount of recycled aggregate and river sand evenly, then add 35% of the formula amount of water and stir evenly, then add the mixture to obtain an intermediate slurry;

[0125] After uniformly mixing the formulated amount of sodium silicate, zinc nitrate, sodium gluconate, polycarboxylate water reducer and the remaining formulated amount of water, the intermediate slurry is added and stirred to obtain the bottom slurry;

[0126] B. Preparation of surface slurry:

[0127] After mixing the formulated quartz sand and 30% of the formulated water evenly, add the formulated P.Ⅱ525 cement, red pigment, polycarboxylic acid water reducer and the remaining formulated water, and mix evenly to obtain the surface slurry;

[0128] C. Preparation of low-cost and high-strength imitation stone surface permeable bricks:

[0129] The bottom layer slurry was injected into the mold and pressed at a pressure of 5 MPa for 0.5 s to form a bottom layer with a thickness of 55 mm;

[0130] The surface layer slurry is injected on the top of the bottom layer in the mold, and pressed for 0.5s at a pressure of 6Mpa to form a surface layer with a thickness of 8mm to obtain an intermediate brick; after the intermediate brick is sealed and cured at 60°C for 8h, a highly permeable and high-strength permeable brick is obtained.

[0131] Example 3

[0132] In this embodiment, the bottom slurry includes the following raw materials calculated by weight: 51 parts of recycled concrete aggregate with a particle size of 10 mm, 32 parts of river sand with a particle size of 0.5 mm and a mud content of ≤3%, 5 parts of mineral powder, 3 parts of water-quenched slag, 12 parts of Class III fly ash, 4 parts of sodium silicate with a modulus of 1.4, 0.8 parts of calcium carbonate whiskers with an aspect ratio of 60, 0.5 parts of PVA fibers with a length of 8 mm and a diameter of 100 μm, 0.8 parts of retarder, 3 parts of water and 0.2 parts of polycarboxylate water reducer; calculated by weight: According to the calculation of mass ratio, the chemical composition of the water-quenched slag includes 30.16% silicon dioxide, 16.41% aluminum oxide, 39.48% calcium oxide, 0.44% iron oxide, 9.40% magnesium oxide, 0.51% sodium oxide, 1.67% titanium dioxide, 0.38% potassium oxide, 0.53% manganese oxide and 1.02% sulfur trioxide; the particle size of the water-quenched slag is 1.0mm; the retarder includes zinc nitrate and sodium gluconate, and according to the mass ratio, the mixing ratio of zinc nitrate and sodium gluconate is 8:2;

[0133] Calculated by mass, the surface layer slurry includes the following raw materials: 65 parts of 40-mesh quartz sand, 15 parts of P.Ⅱ525 cement, 0.5 parts of yellow pigment, 2 parts of water and 0.1 parts of polycarboxylic acid water reducer.

[0134] The method for preparing the high-permeability and high-strength permeable brick of this embodiment comprises the following steps:

[0135] A. Preparation of bottom slurry:

[0136] After mixing the formulated amount of mineral powder, industrial waste slag and fly ash evenly, calcium carbonate whiskers, 30% of the formulated amount of water and fiber are added in sequence, and mixed evenly to obtain a mixture;

[0137] Mix the formula amount of recycled aggregate and river sand evenly, then add 40% of the formula amount of water and stir evenly, then add the mixture to obtain an intermediate slurry;

[0138] After uniformly mixing the formulated amount of sodium silicate, zinc nitrate, sodium gluconate, polycarboxylate water reducer and the remaining formulated amount of water, the intermediate slurry is added and stirred to obtain the bottom slurry;

[0139] B. Preparation of surface slurry:

[0140] After mixing the formulated quartz sand and 35% of the formulated water evenly, add the formulated P.Ⅱ525 cement, red pigment, polycarboxylic acid water reducer and the remaining formulated water, and mix evenly to obtain the surface slurry;

[0141] C. Preparation of low-cost and high-strength imitation stone surface permeable bricks:

[0142] The bottom layer slurry was injected into the mold and pressed at a pressure of 4 Mpa for 0.8 s to form a bottom layer with a thickness of 53 mm;

[0143] The surface layer slurry is injected into the top of the bottom layer in the mold, and pressed for 0.7s at a pressure of 5Mpa to form a surface layer with a thickness of 8mm to obtain an intermediate brick; after the intermediate brick is sealed and cured at 40°C for 12h, a highly permeable and high-strength permeable brick is obtained.

[0144] Comparative Example 1

[0145] The preparation method and raw materials of Comparative Example 1 are the same as those of Example 1, except that no industrial waste residue is added to the bottom slurry formula in Comparative Example 1.

[0146] Comparative Example 2

[0147] The preparation method and raw materials of Comparative Example 2 are the same as those of Example 1, except that no mineral powder is added to the bottom slurry formula in Comparative Example 2.

[0148] Comparative Example 3

[0149] The preparation method and raw materials of Comparative Example 3 are the same as those of Example 1, except that fly ash is not added to the bottom slurry formula in Comparative Example 3.

[0150] Comparative Example 4

[0151] The preparation method and raw materials of Comparative Example 4 are the same as those of Example 1, except that sodium silicate is not added to the bottom slurry formula in Comparative Example 4.

[0152] Comparative Example 5

[0153] The preparation method and raw materials of Comparative Example 5 are the same as those of Example 1, except that the mesh size of the quartz sand in the surface layer slurry formula of Comparative Example 5 is 15 meshes.

[0154] Comparative Example 6

[0155] The preparation method and raw materials of Comparative Example 6 are the same as those of Example 1, except that no calcium carbonate whiskers are added to the bottom slurry formula in Comparative Example 6.

[0156] Comparative Example 7

[0157] The preparation method and raw materials of Comparative Example 7 are the same as those of Example 1, except that PVA fiber is not added to the bottom slurry formula in Comparative Example 7.

[0158] Permeable bricks were prepared by the preparation methods in the above embodiments and comparative examples, and the flexural strength, compressive strength, water permeability coefficient and wear resistance of the obtained permeable bricks were tested using the test method of "GB / T 25993-2010 Permeable Pavement Bricks and Permeable Road Panels". The results are shown in Table 1 below.

[0159] Table 1 Test results of relevant performance of permeable bricks

[0160]

[0161]

[0162] From the performance test results in Table 1, it can be seen that the permeable bricks prepared by the preparation method of a high-permeability and high-strength permeable brick in the present technical scheme have a compressive strength ≥40MPa, a flexural strength ≥8MPa, a permeability coefficient >0.03cm / s, and a grinding pit length ≤35mm. It not only has high permeability and high strength, but also has excellent wear resistance to meet the use requirements.

[0163] In Comparative Example 1, since no industrial waste residue was added, the strength of the bottom slurry deteriorated, thereby affecting the strength of the permeable brick.

[0164] Since no mineral powder was added in Comparative Example 2 and no fly ash was added in Comparative Example 3, the strength of the bottom slurry deteriorated, thereby affecting the strength of the permeable bricks.

[0165] In Comparative Example 4, since sodium silicate was not added, the activity of the mineral powder, industrial waste slag and fly ash could not be activated, and the cementitious material could not be formed to wrap the coarse aggregate and fine aggregate in the base slurry, so the base layer could not be obtained, and thus the permeable bricks could not be produced.

[0166] In Comparative Example 5, since the mesh size of the quartz sand in the surface slurry formula is too small, the porosity of the skeleton formed by the quartz sands interlocking with each other is low, which affects the water permeability and wear resistance.

[0167] Since no calcium carbonate whiskers were added in Comparative Example 6 and no PVA fibers were added in Comparative Example 7, the strength of the underlying slurry deteriorated, thereby affecting the strength of the permeable bricks.

[0168] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.

Claims

1. A high-permeability and high-strength permeable brick, characterized by: It comprises a bottom layer and a surface layer arranged in sequence from bottom to top; the bottom layer is obtained by solidifying the bottom layer slurry, and the surface layer is obtained by solidifying the surface layer slurry; Calculated by weight, the base slurry includes the following raw materials: 50-55 parts of coarse aggregate, 30-35 parts of fine aggregate, 3-5 parts of mineral powder, 3-5 parts of industrial waste slag, 9-12 parts of fly ash, 3-5 parts of sodium silicate, 0.8-1 part of calcium carbonate whisker, 0.2-0.5 part of fiber, 0.7-1 part of retarder, 2-3 parts of water and 0.1-0.2 part of water reducer I; the chemical composition of the industrial waste slag includes silicon dioxide, aluminum oxide and calcium oxide; Calculated by mass, the surface layer slurry includes the following raw materials: 55-65 parts of quartz sand, 15-20 parts of white cement, 0.1-0.5 parts of pigment, 1-2 parts of water and 0.1-0.2 parts of water reducer II; wherein the white cement is P.II525 cement, and the mesh size of the quartz sand is 20-40 meshes.

2. A high-permeability and high-strength permeable brick according to claim 1, characterized in that: The industrial waste slag is water-quenched slag, and the chemical composition of the water-quenched slag, calculated by mass percentage, includes 30-35% silicon dioxide, 15-20% aluminum oxide and 35-40% calcium oxide, and the remainder is ferric oxide, magnesium oxide, sodium oxide, titanium dioxide, potassium oxide, manganese oxide and sulfur trioxide; The particle size of the water-quenched slag is less than 2 mm.

3. The high-permeability and high-strength permeable brick according to claim 1, characterized in that: The aspect ratio of the calcium carbonate whisker is 40-60, the length of the fiber is 6-12 mm, and the diameter is 45-190 μm.

4. The high-permeability and high-strength permeable brick according to claim 1, characterized in that: The fly ash is Grade III fly ash; The modulus of the sodium silicate is 1.2 to 1.

4.

5. The high-permeability and high-strength permeable brick according to claim 1, characterized in that: The thickness of the bottom layer is 50-55 mm, and the thickness of the surface layer is 5-10 mm.

6. The high-permeability and high-strength permeable brick according to claim 1, characterized in that: The coarse aggregate is recycled aggregate, and the particle size of the recycled aggregate is 5 to 10 mm; The fine aggregate is river sand, and the particle size of the river sand is 0.1-0.5 mm. Calculated by mass percentage, the mud content of the river sand is ≤3%.

7. The high-permeability and high-strength permeable brick according to claim 1, characterized in that: The retarder includes zinc nitrate and sodium gluconate; Calculated by mass ratio, the mixing ratio of the zinc nitrate and the sodium gluconate is (6-8): (2-4).

8. A method for preparing a high-permeability and high-strength permeable brick, characterized in that: The method for preparing the low-cost and high-strength imitation stone surface permeable brick as claimed in any one of claims 1 to 7 comprises the following steps: A. Preparation of bottom slurry: After mixing the formulated amount of mineral powder, industrial waste slag and fly ash uniformly, calcium carbonate whiskers, part of the formulated amount of water and fiber are added in sequence, and mixed uniformly to obtain a mixture; The coarse aggregate and fine aggregate of the formula amount are mixed evenly, and then part of the formula amount of water is added and stirred evenly, and then the mixture is added to obtain an intermediate slurry; After uniformly mixing the formulated amount of sodium silicate, retarder, water reducer I and the remaining formulated amount of water, the intermediate slurry is added and stirred to obtain the bottom slurry; B. Preparation of surface slurry: After mixing the formulated amount of quartz sand and part of the formulated amount of water evenly, add the formulated amount of white cement, pigment, water reducing agent II and the remaining formulated amount of water, and mix evenly to obtain the surface slurry; C. Preparation of low-cost and high-strength imitation stone surface permeable bricks: The bottom layer slurry is injected into the mold and initially pressed to form the bottom layer; The surface layer slurry is injected on the top of the bottom layer in the mold, and the surface layer is formed by re-pressing to obtain the middle brick; After the middle brick is sealed and steam cured, a high-permeability and high-strength permeable brick is obtained.

9. The high-permeability and high-strength permeable brick according to claim 8, characterized in that: In step C, the initial pressure is 3-5 MPa, and the initial pressure time is 0.5-1 s; The re-pressing pressure of the re-pressing is 4-6 MPa, and the initial pressing time is 0.5-1 s; The curing temperature of the steam curing is 40-60° C., and the curing time is 8-12 hours.

10. The high-permeability and high-strength permeable brick according to claim 8, characterized in that: In step C, the compressive strength of the permeable brick is ≥40MPa, the flexural strength is ≥8MPa, the permeability coefficient is >0.03cm / s, and the grinding pit length is ≤35mm.

Citation Information

Patent Citations

  • Anti-efflorescence paving stone and preparation method thereof

    CN117447143A